Trio Album for violin, violoncello & piano, vol. V Piano part - BARGIEL, Waldemar [et.al] (The Boston Music Co.)
Andante sostenutonLentonThe bellsnRomance sans parolesnEpithalamenBoleronBarcarollenSerenadenWaltz-ScherzonCanzonetta